Enhancement of shear stability of a Fe-based amorphous alloy using electrodeposited Ni layers. Issue 12 (December 2018) - Wang, Y.C.; Luo, X.M.; Chen, L.J.; Yang, H.W.; Zhang, B.; Zhang, G.P.
Abstract: Tensile and fracture behaviors of sandwich-structured composites consisting of a Fe-based amorphous layer with a constant thickness and ultrafine-grained Ni layers with different thicknesses were investigated. The results indicate that the initiation and the stable propagation of the shear band in the amorphous layer was dominated by the Ni layers due to their strong constraint role. The catastrophic fracture of the amorphous layer was postponed in the sandwich composites through properly increasing the constrained Ni layer thickness, which effectively decreased the shear stress on the shear fracture planes of the amorphous layer, and thus led to stable propagation of the primary SB characterized by the increase in the smooth region size of the shear band.